Possible roles of AMPK and macropinocytosis in the defense responses against Δ9-THC toxicity on HL-1 cardiomyocytes. (2021) - Murata, Tatsuhiko; Noritake, Kanako; Aki, Toshihiko; Uemura, Koichi
Graphical abstract: Highlights: Δ 9 -THC induced ER stress in HL-1 murine cardiomyocyte. Δ 9 -THC also induced macropinocytosis, which was mediated by AMPK. AMPK-macropinocytosis axis was one of the survival pathways against Δ 9 -THC. Abstract: Cannabinoids are some of the most popular recreationally used illicit drugs, and are frequently consumed along with alcoholic beverages. Although the whole body effects of cannabinoids depend largely on their effects on the central nerve system, cannabinoids could harm the heart directly, due to the presence of the endocannabinoid system including cannabinoid receptor1 and 2 (CB-R1 and CB-R2) in the heart. The aim of this study is to examine the mechanism of direct cardiotoxicity of Δ 9 -tetrahydrocannabinol (Δ 9 -THC), the main psychoactive ingredient of cannabis. For this purpose, HL-1 murine atrial cardiac muscle cells were treated with 10 or 30 μM Δ 9 -THC, along with 100 mM ethanol to examine the possible synergistic effects of Δ 9 -THC and ethanol. Transcriptome analysis showed upregulation of the genes involved in the unfolded protein response (UPR), including Bip, CHOP, ATF4 and ATF6, in cells treated with Δ 9 -THC. Immunoblot analysis showed caspase3 activation, indicating apoptosis caused by ER stress in Δ 9 -THC-treated cells. Microscopic analysis showed that Δ 9 -THC enhances macropinocytosis, a process involved in the uptake of extracellular fluids including nutrients. Moreover Δ 9 -THC seemed to activate AMPK, a sensor of intracellular energy status and an activator of macropinocytosis. Finally, we found that compound C (AMPK inhibitor) aggravated cell death by Δ 9 -THC while AICAR (AMPK activator) ameliorated it. Collectively, these results indicate that the activation of AMPK is necessary for the survival of HL-1 cells against Δ 9 -THC toxicity. Macropinocytosis might serve as one of the survival pathways downstream of AMPK.